Unintended Economic Consequences of Biotrade in Namibian Marula Plant Oil: a Study of Changing Patterns of Economic Behaviour (2014)
Marula fruit are traditionally gathered and processed as an important women’s collaborative activity in the north central region of Namibia. After the abolition of apartheid, the end of the Cold War, and the expansion of commodification of marula food products, the commercialization of marula oil production was supported through formation of a women’s cooperative and the establishment of two international biotrade contracts, with the aim to empower local women and the poor. This study conducts an institutional analysis of changes in rules concerning marula use, understood as impacts from biotrade. Findings reveal that gender, power asymmetries and unstable social contexts have influenced the changes in rules that came with implementation of marula oil biotrade in Namibia.